THE YPRESIAN FISHES OF THE SOLTERI LAGERSTÄTTE (TRENTO, NORTHERN ITALY): A GLIMPSE INTO THE EARLY EOCENE TETHYAN MESOPELAGIC ASSEMBLAGES (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
A Ypresian fish-bearing site was discovered in the late 1970s at Solteri (Trento, northern Italy), but its ichthyofauna, dominated by pelagic bony fishes, remained almost completely neglected for decades despite its potential interest. In fact, it represents the nearly coeval pelagic equivalent of the Lagerstätten of Bolca (Verona province, northeastern Italy), worldwide known for their extremely abundant and diversified, reef-associated fish fauna. The Solteri ichthyofauna, represented by almost 300 specimens, comprises what appears to be a mesopelagic assemblage including stomiiforms (Gonostomatidae and Phosichthyidae), myctophiforms (Myctophidae) and certain percomorphs (Gempylidae and Centrolophidae), most of them represented by new, so far undescribed taxa, of which the following are established herein: Ammutichthys loricatus n. gen. et sp., Eogorgon bizzarinii n. gen. et sp., Eomyctophum mainardii n. sp., Erebusia tenebrae n. gen. et sp. Krampusichthys tridentinus n. gen. et sp., Laurinichthys boschelei n. gen. et sp., Scopeloides bellator n. sp., Scopeloides violator n. sp., Solterichthys macrognathus n. gen. et sp., and Wudelenia diabolica n. gen. et sp. Solteri is of extreme relevance not only because it represents one of the most ancient Cenozoic deep-water Lagerstätten known, but it also allows us to define the structure of the western Tethyan pelagic fish communities during the demise of the Early Eocene Climatic Optimum (EECO), the interval of the Cenozoic with the warmest long-term global average temperature and highest CO2 levels (Filippi et al. 2024).
Keywords: bathyal; Teleostei; taxonomy; new taxa; early Paleogene; Tethys.